The Prototype of e-SRC Voting System - Izliyana, Ismail (2010)
This project will be a feasibility study on the implementation of electronic voting or e-voting in the Students Representative Council (SRC) election in Matriculation Colleges. An electronic voting technique, such as Direct Recording Electronic (DRE) has become a new alternative in election nowadays. It has been implemented widely. The emergence of ICT in Malaysia had made the implementation of DRE is possible. DRE offers benefits in term of time consuming and to solve overvote and undervote problem. This project will be developed based on Hevner's Methodology (2004) which consist five phases. The system will be developed based on requirements and needs in SRC election. Finally the system will be tested and the result will showed the suitability and possibility of the system implementation to be implemented in matriculation colleges.